Recharging the battery: placement tests for ESP students - Oliveira, Lucia Pacheco de; Miller, Inés Kayon de; Martins, Márcia do Amaral Peixoto; Cunha, Maria Isabel Azevedo; Brown, James Dean (UNESP, 2001)
This paper first reviews key concepts in language testing and discusses the use of the English Language Placement Test administered at the Catholic University of Rio de Janeiro to computer science students, who are required t o take one of the two ESP courses offered by the English program. The analysis of the scores on two versions of a test administered to two different groups of computer science students who took the examination in sequential semesters is presented. For the original test, it em facility and it em discrimination were calculated, then overall test reliability was estimated. The statistics were carefully examined and a number of t he test items were eliminated, revamped or replaced in creating a revised version of the test. This modified and improved version of the test was then administered to a second group of students and the same statistics were applied once more. The results are discussed in terms of the importance of item analysis and revision for providing more consistent and accurate language testing instruments.